Antinociceptive and anti-inflammatory activities of Tinospora crispa in various animal models - Sulaiman, Mohd Roslan; Zakaria, Zainul Amiruddin; Lihan, R. (Medwell Journals, 2008)
The present study was carried out to determine the antinociceptive and anti-inflammatory activities of the ethanol extract of Tinospora crispa stem. The antinociceptive activity was measured using the writhing and hot plate tests, while, the anti-inflammatory was measured using the carrageenan-induced paw edema test. The air-dried stems of L. japonica were soaked in ethanol (1:5; w/v) at the temperature of 48°C for 48 h. The supernatant collected was evaporated under reduced pressure and kept at -80°C until used. Prior to each experiment, the extract was dissolved in distilled water (dH2O) to prepare the doses of 30, 100 and 300 mg kg 1. The extract administered intraperitoneally exhibited significant (p<0.05) antinociceptive and anti-inflammatory activities in a dose-dependent manner in all assays used.